2000
DOI: 10.1002/chin.200037272
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Polycyclic Fluoroquinolinones

Abstract: organic chemistry, review organic chemistry, review Z 0200 37 -272 Polycyclic Fluoroquinolinones -[methods of synthesis; 112 refs.]. -(MOKRUSHINA, G. A.; NOSOVA, E. V.; LIPUNOVA, G. N.; CHARUSHIN, V. N.; Russ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The effect of substituents at certain positions is unequivocal (3,4), while at certain positions, e.g., 6, it depends on the substituent at position 8. Thus, an unfavorable substituent at position 6 will be advantageous with the "right" substituents at positions 1, 3, and 8 [5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of substituents at certain positions is unequivocal (3,4), while at certain positions, e.g., 6, it depends on the substituent at position 8. Thus, an unfavorable substituent at position 6 will be advantageous with the "right" substituents at positions 1, 3, and 8 [5].…”
Section: Methodsmentioning
confidence: 99%
“…Replacement of the N atom by an O or C atom deactivates the molecule [4]. The best is an ethyl group at the N atom and also its bioisosteres -cyclopropyl [64, 102-104, 110, 116], tert-butyl [64], methylamino, 2,(4)-(di)fluorophenyl, p-hydroxyphenyl [3], fluorocyclopropyl [97,13], 5-amino-2,4-difluorophenyl, 5-fluoro-2-pyridinyl, 2-amino-3,5-difluoro-2-pyridinyl [13], piperidinyl, piperazinyl [110], and 4-amino-2-fluorophenyl [73] substituents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2-Mercapto-5,6-difluorobenzimidazole 1 was shown to react with aromatic α-haloketones to give 2-phenacylthio-5,6-difluorobenzimidazoles 2. The latter were transformed by acylation and cyclodehydration in an acetic anhydride-pyridine system into benzo [4,5] [13]. Biological tests revealed that compound 4 (Ar = C 6 H 5 ) displayed a considerable activity toward the meastle virus [14].…”
Section: Fluorinated Benzazolesmentioning
confidence: 98%
“…have been advanced [2]. A great deal of publications focus on structural modifications of fluoroquinolones as inhibitors of the DNA-gyrase (bacterial topoisomerase), the enzyme that is responsible for cleavage and renovation of the double helix of bacterial DNA [3][4][5]. It has been shown that fluoroquinolones can influence the eucariot cells, sometimes showing a high cytotoxicity, and thus being of interest as anticancer agents [6,7].…”
Section: Introductionmentioning
confidence: 99%